Transportable setup for amplifier phase fidelity measurements. (April 2015) - Tröbs, M; Bogan, C; Barke, S; Kühn, G; Reiche, J; Heinzel, G; Danzmann, K
Abstract: One possible laser source for the Laser Interferometer Space Antenna (LISA) consists of an Ytterbium-doped fiber amplifier originally developed for inter-satellite communication, seeded by the laser used for the technology demonstrator mission LISA Pathfinder. LISA needs to transmit clock information between its three spacecraft to correct for phase noise between the clocks on the individual spacecraft. For this purpose phase modulation sidebands at GHz frequencies will be imprinted on the laser beams between spacecraft. Differential phase noise between the carrier and a sideband introduced within the optical chain must be very low. We report on a transportable setup to measure the phase fidelity of optical amplifiers.